Histories, Poetry, Haunting - Nellis, Robert Christopher (Journal of the Canadian Association for Curriculum Studies, 2020)
How do histories of this land inform, whisper in the ear and trouble its curricular landscapes? This presentation explores some accounts of pasts, histories and their lingering effects and affects, both in their failures and their unique re-arrivals. What would be some implications of imagining the past, not as a presumably singular, monolithic, universality anchored to a relationship with a presumably static, temporalized subjectivity? What of curricular re-imaginings toward, not Past, but pasts; moreover, pasts that dwell in the footprints laid there, but also refuse to remain there--that keep returning, as revenant? Work informed by Munslow (2010) might suggest that the stories one tells of pasts may be as important as the content of those narratives. The present work moves within a space of considering text, especially creative and poetic work, as offering a modality uniquely attuned to resonances of pasts that are both grounded and fluid. The work imagines a space with enough room for both particularities and their otherwise. It imagines them holding hands in a spectral partnership--conjuring ghosts, if ever unwelcome, nonetheless returning as figures of reminding, offerers of histories, characters of reckoning.